Participative farmer testing of four low external input technologies, to address soil fertility decline in Mono Province( Benin) - Versteeg, M.; Koudokpon, V. (Elsevier, 1993)
Farmer participation in experimenting with technologies in Mono province (Benin) increased when attention was focused on their major problems. One such problem is soil degradation caused by over-exploitation of land. Four different low external input technologies, all with leguminous components and half of them based on agroforestry, have been tested since 1990 by sub-groups of farmers, who all belong to a discussion group focussing on this problem. The technologies are: (i) a short season fallow of Mucuna pruriens var. utilis; (ii) an improved perennial tree fallow of Acacia auriculiformis; (iii) a short season fallow of pigeonpea; and (iv) an alley-cropping system on the basis of alternating hedgerows of Gliricidia sepium and Leucaena leucocephala. The first two technologies were aimed at the regeneration of very degraded plots, while the latter two technologies concentrate on stabilising still moderately fertile land. Some impressions and results are discussed.